How do North Korean refugees in South Korea utilize social support to cope with acculturative stress? - Soim Park; Jennifer A. Wenzel; Pamela J. Surkan (Elsevier, 2023)
Geographic resettlement induces acculturative stress in refugees. In response, they utilize social support to deal with acculturative stress and to adapt to the host community. In this study we sought to understand how North Korean refugees (NKRs) utilize social support to reduce acculturative stress. We conducted semi-structured interviews with 30 NKRs in South Korea and 20 South Koreans (SKs) who were friends or acquaintances of NKRs. Purposive and snowballing sampling strategies were used to recruit participants at two sites. Following a Grounded Theory approach, we analyzed the data using initial coding, focused coding, and constant comparison. We found that NKR participants coped with loneliness by exchanging emotional support with other NKRs who share their lived experiences and by building solidarity with them. NKRs described expanding their social networks to include SKs in order to assimilate into their communities. Many SKs tried to develop family-like relationships with NKRs. While SKs were important resources for informational or instrumental support early on, their roles were sometimes replaced by other NKRs as social ties among NKRs were strengthened. All NKRs who reported that they strategically approached SKs to learn about South Korean culture had held full-time jobs and appeared to be better adjusted to South Korea. Appraisal support was the least reported type of social support, but some NKRs tried to deal with social discrimination through positive appraisal. To reduce acculturative stress, NKRs sought varied types of social support from different kinds of social network members. Findings highlight the need to diversify and strengthen social support for NKRs, thereby fostering coping strategies and reducing acculturative stress.